2021
DOI: 10.1007/s10461-021-03410-w
|View full text |Cite
|
Sign up to set email alerts
|

Water Insecurity is Associated with Lack of Viral Suppression and Greater Odds of AIDS-Defining Illnesses Among Adults with HIV in Western Kenya

Abstract: Reliable access to safe and acceptable water in sufficient quantities (i.e., water security) is important for medication adherence and limiting pathogen exposure, yet prior studies have only considered the role of food security as a social determinant of HIV-related health. Therefore, the objective of this analysis was to assess the relationships between household water insecurity and HIV-related outcomes among adults living with HIV in western Kenya (N = 716). We conducted a cross-sectional analysis of baseli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 43 publications
(65 reference statements)
1
15
0
Order By: Relevance
“…This is comparable with the study that was reported from South Africa (4%), 20 Tanzania (3%), 21 and Nigeria (4.2%). 22 However, the result is much higher than the studies conducted in Iran (1.7%), 23 Australia (2.1%), 24 Kenya (1.5%), 25 and Tunisia (1.7%). 26 This discrepancy may be due to variation among the study participants, a lack of PPE, a higher patient load, and the infrequent use of PPE among participants in this study setting.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…This is comparable with the study that was reported from South Africa (4%), 20 Tanzania (3%), 21 and Nigeria (4.2%). 22 However, the result is much higher than the studies conducted in Iran (1.7%), 23 Australia (2.1%), 24 Kenya (1.5%), 25 and Tunisia (1.7%). 26 This discrepancy may be due to variation among the study participants, a lack of PPE, a higher patient load, and the infrequent use of PPE among participants in this study setting.…”
Section: Discussionmentioning
confidence: 64%
“…This is supported by many studies, such as those in Tunisia, 26 South Africa, 20 and Kenya. 25 The reason could be described as the availability of PPE in healthcare facilities influencing HCWs’ habits of using PPE during patient care and procedures, thereby reducing exposure to HIV and its impact on the outcome of exposure. Furthermore, the infrequent availability of PPE reduced HCWs’ compliance to wear PPE such as a glove, face mask, face shield, and apron, potentially amplifying their exposure to HIV infection; and finally, increasing the transmission of blood-borne pathogens.…”
Section: Discussionmentioning
confidence: 99%
“…HCWs who were midwives had four times higher odds of testing positive for HIV (AOR = 4.2, 95% CI: 3.17, 8.21). This is supported by many studies, such as those in Tunisia [27], South Africa [21], and Kenya [26]. The reason could be described as the availability of PPE in healthcare facilities, influencing HCWs' habits of using PPE during patient care and procedures, thereby reducing exposure to HIV and its impact on the outcome of exposure.…”
Section: Discussionmentioning
confidence: 80%
“…In this case, women who have experienced injuries or been subjected to violence are less physically able to collect water, creating further risk for scarcity in the household and related repercussions for nutrition and health. Water insecurity co‐occurs and exacerbates food insecurity (Brewis et al, 2020; Wutich & Brewis, 2014), HIV (Krumdieck et al, 2016; Nagata et al, 2021; Workman & Ureksoy, 2017), and COVID‐19 (Adams et al, 2021; Staddon et al, 2020; Stoler, Jepson, & Wutich, 2020). Water is also integral to sanitation and hygiene (Choudhary et al, 2020), increasing the potential for deleterious, syndemic interactions between water‐related infectious diseases, malnutrition, and dehydration.…”
Section: Discussionmentioning
confidence: 99%